Association between endometriosis and sexual satisfaction among a sample of lebanese women - Maya Kfoury; Habib Barakat; Souheil Hallit; Sahar Saliba (BMC, 2023)
Abstract Background Endometriosis is a complex disease that affects approximately 10% of women of childbearing age. It is characterized by the presence of endometrial-like tissue outside the uterus and often results in symptoms such as pelvic pain and infertility. This condition may disturb mental health and decrease both the mental and physical health related quality of life of women. The aim of this study was to assess the emotional state and the intimate relational aspect of life in Lebanese women living with endometriosis. Methods This is a case-control study that included 317 women (65 participants with endometriosis and 252 controls (1:3 ratio)). Participants completed an online survey that included questions related to endometriosis, Sexual Satisfaction Scale for Women, Couple Satisfaction Index, Perceived Partner Responsiveness Scale and the Depression, Anxiety and Stress Scale. Results A significantly higher mean sexual satisfaction score was found in women without endometriosis compared to those with endometriosis (90.83 vs. 83.42; p = 0.006). No significant difference was found in terms of couple satisfaction, depression, anxiety, stress, and perceived partner responsiveness between the two groups. Higher couple satisfaction (Beta = 1.30) and perceived partner responsiveness (Beta = 0.16) were significantly associated with higher sexual satisfaction, whereas higher depression (Beta=-1.70) and having endometriosis compared to not (Beta=-6.51) were significantly associated with lower sexual satisfaction. Conclusion This study validated the link between endometriosis and sexual satisfaction and invalidated the association between endometriosis and emotional state, as well as couple satisfaction and perceived partner responsiveness. Greater sexual satisfaction was, however, linked to greater perceived partner responsiveness and greater couple satisfaction, as well as decreased signs of depression, anxiety, and stress. More research is warranted to better understand how Lebanese women are coping with the disease and how clinicians may help them further.